Intercultural interpretations about concepts of nutrition: body formation among the tikuna indians of the colombian amazon trapeze (2011)
This paper approaches the indigenous perceptions about the formation of an infant body by the Tikuna Indians of San Martin de Amacayacu, who live in the south of the Colombian Amazon Trapeze. Indigenous concepts about nutrition are not comparable with the concepts of nutrition and malnutrition from the perspective of biological quantification. For the natives, body formation initiates with their myths of origin, everyday subsistence activities, relationships with natural beings and the bestowal of care of infant babies and small children. For health professionals, in contrast, the conception of the human body is based upon a biological, nutritional and anthropometric logic. The article shows the differences between these two visions, calling for an intercultural rethinking to make them compatible in order to avoid infant deaths associated with nutritional deficiencies.